REG 562 - Building Services Technology - December 2013 / January 2014 - PPPBP, Pusat Pengajian Perumahan Bangunan Dan Perancangan (2013)
First Semester Examination 2013/2014 Academic Session December 2013 / January 2014 Duration : 3 hours